Public Speaking for Teen Learners: Membangun Keberanian Berbicara Bahasa Inggris - Wulandari, Fitri; Suryanti, Nunuk; Suyono, Akhmad; Sari, Cyintia Kumala; Al-Fajri, Rahmad (Universitas Pahlawan Tuanku Tambusai, 2026)
This Community Service Program aims to improve students’ confidence in speaking English in public through the Public Speaking for Teen Learners activity. The program was conducted at SMP IT Imam Syafi’i Cendikia Pekanbaru and involved students in an active learning approach that included interactive workshops, practice sessions, and performance simulations. Data were collected through observation, pre-test, and post-test speaking confidence measurements. The results indicate significant improvement in students’ confidence, fluency, vocal techniques, body language, and their ability to deliver English speeches effectively. Moreover, a supportive learning environment and a structured training model helped reduce students’ speaking anxiety. Therefore, this program is considered effective in developing students’ public speaking skills and is recommended to be continued through the establishment of an English Public Speaking Club as a sustainable follow-up program.